Changes in biochemical and sperm parameters of rats drinking energy drinks: Effects of energy drinks on biochemical and sperm parameters - N. Jafar, Sarwar (Cellular and Molecular Biology, 2024)
Tiger energy drink is used in this research to see the effect on serum lipid profile, liver enzymes, and kidney function, also observing changes in sperm parameters. Sixteen male rats were divided into four groups, each consisting of four rats. The control group was given water and rat feed, while groups 1, 2, and 3 were given water with Tiger energy drink (25%, 50%, and 75%, respectively) for eight weeks. The results showed that the effect of energy drinks on lipid profile decreased cholesterol, TG, and LDL, while there was a slight increase in HDL. Treatment with wild Tiger energy drink generally caused insignificant increases in GOT and GPT in both G2 and G3 groups as compared to the control. However, in the G1 group, GPT and GOT significantly increased. Accordingly, ALP concentration was significantly increased in all experimental groups compared to the control group. Sperm quality declined as the concentration of energy drinks consumed increased. The potential adverse effects of energy drinks, at their specific dosages, have been determined to include hepatic and renal impairment, as well as alterations in serum lipids. Additional research is required to investigate the specific mechanism by which energy drinks impact spermatogenesis, either through the modulation of endocrine hormones or other metabolic pathways.